ANALISIS PERSEDIAN BAHAN BAKU SARUNG TANGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) DI CV. CAHAYA SETIA MULIA - Arief Eka Kurniawan; Ayudyah Eka Apsari (CV. ALIM'SPUBLISHING, 2025)
In March, CV. Cahaya Setia Mulia produced 2,000 units of gloves. Based on analysis with the Overall Equipment Effectiveness (OEE) method, an OEE value of 53.71% was obtained, which is still below the ideal OEE standard of 85%. The low production effectiveness was mainly caused by Reduce Speed Losses, which contributed 50% to the decline in performance. This problem arose due to a decrease in production speed below the standard caused by delays in the supply of raw materials. To overcome this problem, a raw material inventory management system is needed that can ensure the availability of raw materials in the right amount, at the right time, and at an efficient cost. Based on cost analysis using the Material Requirement Planning (MRP) method, the Lot For Lot (LFL) technique proved to be the most efficient with a total cost of Rp 45,018,000, because it does not involve raw material storage costs. In comparison, the Economic Order Quantity (EOQ) technique resulted in a total cost of Rp 76,369,950, while the Period Order Quantity (POQ) technique recorded the highest total cost of Rp 81,860,000. High costs in the POQ method are caused by the storage of raw materials that exceed production needs.